L-band spectra of 13 outbursting Be Stars - Mennickent, R. E. (2009)
We present new L-band spectra of 13 outbursting Be stars obtained with ISAAC at the ESO Paranal Observatory. These stars can be classified in three groups depending on the presence or absence of emission lines and the strength of Br alpha and Pf gamma emission lines relative to those of Humphreys lines from transitions 6-14 to the end of the series. These groups are representative of circumstellar envelopes with different optical depths. For the group showing Br alpha and Pf gamma lines stronger than Humphreys lines, the Humphreys decrement roughly follows the Menzel case-B for optically thin conditions. For the group showing comparable Br alpha, Pf gamma, and Humphreys emission-line strengths, the Humphreys decrements moves from an optically thin to an optically thick regime at a transition wavelength that is characteristic for each star but typically is located around 3.65-3.75 ìm (transitions 6-19 and 6-17). Higher-order Humphreys lines probe optically thin inner regions even in the optically thicker envelopes. We find evidence of larger broadening in the infrared emission lines compared with optical lines, probably reflecting larger vertical velocity fields near the star. The existence of the aforementioned groups is in principle consistent with the description recently proposed by de Wit et al. for Be star outbursts in terms of the ejection of an optically thick disk that expands and becomes optically thin before dissipation into the interstellar medium. Time-resolved L-band spectroscopy sampling the outburst cycle promises to be an unique tool for testing Be star disk evolution.